PEREMPUAN DI RUANG PUBLIK DALAM PERSFEKTIF HADIS - Nafriandi Nafriandi (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Religion, in the past time, was flourished by servitude system. Therefore, there are more words in religious literature related to slavery issues. The words also implicitly indicated the superiority of man position to women in some degrees. In Jahiliyah time, there were customs and bad habits that related to woman. Woman felt more inferior to men in the freedom of status context. Accordingly, Al-Qur’an presented to escalate the social status of women and against the negative tradition and customs that had been prevalent. This article tries to analyze hadits perspective on regarding woman in public space.